THE SHOREFACE - FAIRWEATHER WAVE BASE ENVIRONMENT OF THE MIDMIOCENE SANDSTONE IN THE CENTRAL PART OF THE MADURA ISLAND - MAC. Endharto (Testing Center for Oil and Gas LEMIGAS, 2006)
As mentioned in the previous paper (Endharto, 2005) this paper is part of the series of the depositional model of the Ngrayong Sandstone, which takes part especially in the central part of the Madura Island. This study also examines physical evidence of the best exposure of the study area. The central part is located between 07 01' 18